Stand Up to Work: assessing the health impact of adjustable workstations. Issue 2 (4th May 2018) - Garland, Elizabeth; Watts, Abigail; Doucette, John; Foley, Mary; Senerat, Araliya; Sanchez, Sadie
Abstract : Purpose: Sedentary behavior is linked to health risks, and prolonged sitting is prevalent among office workers. Adjustable workstations (AWS) promote health by allowing transitions between sitting and standing. Stand Up to Work compares workers with AWS to traditional desks (TD). The paper aims to discuss these issues. Design/methodology/approach: Employees were randomly selected from one office floor to receive AWS, two identical floors maintained TD. Participants received workplace wellness and ergonomic training, completed self-administered questionnaires, and responded to repeated micropolling at baseline (T0), 3 (T1), 6 (T2), and 12 (T3) months in Atlanta, 2015-2016. Groups were compared using two-sample t -tests and nonparametric Wilcoxon tests. Findings: Compared to TD ( n = 24), participants with AWS ( n = 24) reported significantly less sedentary behavior at T1 and T2 after AWS installation ( p <0.05), with a retention rate at T2 of 80 and 65 percent for the AWS and TD group, respectively. In all, 47 percent of participants with AWS reported decline in upper back, shoulder, and neck discomfort ( p =0.04); 88 percent of AWS participants reported convenience to use, 65 percent reported increased productivity, and 65 percent reported positive impact outside the workplace. Individuals with normal or underweight body mass index (BMI) reported a significantly greater decline in percent of time sitting compared to participants with overweight or obese BMI at all three time points. Originality/value: AWS are beneficial in reducing sedentary behavior in and outside the workplace. Behavioral changes were sustained over time and associated with less self-reported muscle pain, more self-reported energy, and awareness of standing. When considering total worker health, employers should include options for AWS to promote reducing sedentary behavior.